Antecedents of E-wallet Usage Intention: An Empirical Study - Dr Jobin Sahadevan (International Journal of Engineering and Management Research, 2023)
Nowadays, the importance of cashless transactions is increasing due to the advancement of technology, especially in the post-pandemic era. An e-wallet is an application that helps users make payments through a mobile device instead of cash. With the advent of e-wallets, people are shifting from using cash to cashless in the era of smartphone technology. This study aims to explore the antecedent factors affecting the intention to use e-wallets as a payment mechanism among young adults in Kerala, India. The study was conducted by following an extended Technology Acceptance Model (TAM) and a Unified Theory of Acceptance and Use of Technology (UTAUT). Data were collected from 380 users of e-wallets, and the data were analyzed using partial least squares structural equation modelling (PLS-SEM) following a two-step approach. The results of the path analysis showed that perceived usefulness and perceived ease of use are the most significant predictors of usage intention for e-wallets, followed by perceived trust and perceived risk. It is also revealed that perceived security does not affect the usage intention of e-wallets. The results will help policymakers make strategic decisions considering customer perceptions of usage intentions.